KAJIAN TERAPAN SUSTAINABLE DESIGN PADA RUANG-BANGUNAN PUSAT PENDIDIKAN ALAM DAN BUDAYA KALIANDRA SEJATI DI PASURUAN, JAWA TIMUR - Hendry, Vivi (Dimensi Interior, 2014)
The other reaction of crisis environment is sustainable design concept. Sustainable design as a part of sustainable development paid attention the balance of three aspects that is social, economy, and ecology. This research studies about applied effort in Pusat Pendidikan Alam dan Budaya (PPAB) Kaliandra Sejati and the result of applied evaluation. PPAB as a place for activities of nature and culture education is designed to have the balance and sustainable mutual relation with its environment. But, the result of analysis revealed that an effort to sustainable design is not easy to be applied, there is many obstacle that causes the unbalance of three aspects. The biggest focus that applied in PPAB is social aspect, then ecology and economy.